Neurocognitive and Mental Health Effects of Spaceflight, Spaceflight Analogs, and Extreme Environments - Marina Corrêa Freitas; Ana Beatriz Freitas Zagari Costa; Fabrício Corrêa Veloso; Letícia da Fonseca Paulo Andrade (Journal of Biomedical & Space Sciences (JBSS), 2026)
Long-duration spaceflight and terrestrial spaceflight analogs expose crews to microgravity, fluid redistribution, altered vestibular and sensorimotor inputs, isolation, confinement, circadian disruption, operational stress, and environmental monotony, potentially affecting neurocognitive performance and mental health. This PRISMA 2020-informed systematic review synthesized empirical human evidence on cognitive, psychological, sleep-related, stress-related, and behavioral outcomes in real and simulated spaceflight environments. Searches were conducted in PubMed/MEDLINE, PubMed Central, ScienceDirect, Frontiers, PLOS, NASA/ESA resources, Google Scholar/Crossref, and reference lists. Eligible studies reported neurocognitive or mental health outcomes during spaceflight, spaceflight analogs, or isolated, confined, and extreme environments. Reviews, editorials, non-human studies, and studies without relevant outcomes were excluded. Eighty-six records were identified; 21 duplicates were removed; 65 records were screened; 27 full texts were assessed; and 20 studies were included in qualitative synthesis. Meta-analysis was not performed because of heterogeneity in settings, designs, samples, instruments, and outcomes. The most consistent findings involved sleep disruption, altered alertness, mood fluctuations, stress responses, behavioral adaptation, and variable changes in vigilance, processing speed, attention, and cognitive throughput. Potential mechanisms include adaptive neuroplasticity, intracranial fluid shifts, neuroinflammatory signaling, and microglial activation. Exercise, structured routines, sleep protection, and individualized monitoring emerged as promising countermeasures. Standardized longitudinal protocols are needed for future missions.